Approaches to the Examination of the Practice of Monitoring "Big Data" of a Socio-Economic Nature - Polyakova, Aleksandra (International Journal of Psychosocial Rehabilitation, 2020)
The article considers approaches to the examining of the practice of monitoring "big data" of a socio-economic nature. Big data, which is an array of structured and unstructured data that is difficult to process using traditional methods, has significant potential, allowing you to get online rapid diagnostic results, examine the entire data set, rather than samples, and use various machine algorithms that identify implicit relationships. The author of the article considers social scoring as promising by marketers, specialists in personnel search and bailiffs, collection and detective agencies for searching debtors in social networks, collecting data, and identifying relationships. It should be noted that many are not ready for data inspection, despite the fact that the automation of business processes in this area has been active for more than 15 years in Russia. For example, in the field of HR Analytics, this is due to the fact that a relatively small number of companies have implemented ERP systems that allow one to accumulate the necessary data, as well as the HR specialists themselves do not save all the data.